Analisis Waktu Penyediaan Berkas Rekam Medis Rawat Jalan di Rumah Sakit Setia Mitra Jakarta Selatan - Hudiyati Agustini; Ririn Sri Lestari; Joko Asmoro W (MEDICORDHIF Jurnal Rekam Medis, 2023)
Provision of medical record files must be able to support health services, including outpatient services at hospitals. The time for providing medical record files since the old patient registered has a service standard of 10 minutes or less. The purpose of this study was to find out when to provide outpatient medical record files at Setia Mitra Hospital. The research design used was observative and quantitative descriptive, with a total sample of 98 medical record files taken by random sampling. The results showed that the average provision of outpatient medical record files was 11 minutes, of which 0 files (0%) within 1−5 minutes, 43 files (43.9%) within 6−10 minutes, 49 files (50.0%) within 11−15%, and 6 files (6.1%) within 16−20 minutes. Factors causing this delay include disruption to the network connection on the TMU printer machine and registration computer, misplaced files (miss files), and the lack of socialization and evaluation of the SPO which regulates the time for providing medical record files. Keywords : delays, provision, time line, outpatient medical record file.